2017
DOI: 10.1016/j.ultsonch.2017.03.035
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-art on ultrasonic oil production technique for EOR in China

Abstract: Ultrasonic oil production technique for enhanced oil recovery (EOR) attracts more attention due to its high adaptability, simple operation, low cost and zero pollution to the oil reservoir. In this paper, recent new downhole tools used for enhanced oil recovery developed in China are summarized. Furthermore, research advance on some key problems that affect the widespread application of ultrasonic oil production technique in China are also summarized in view of what are the primary factors that influence crude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Application results showed that the average oil recovery can be increased by 6-9%. In addition, paraffin deposition and antiscaling viscosity of crude oil can be inhibited and reduced effectively [12].…”
Section: China Expertise In Eormentioning
confidence: 99%
“…Application results showed that the average oil recovery can be increased by 6-9%. In addition, paraffin deposition and antiscaling viscosity of crude oil can be inhibited and reduced effectively [12].…”
Section: China Expertise In Eormentioning
confidence: 99%
“…Ultrasonic enhanced oil recovery technology has been applied in many aspects of petroleum industry, including demulsification by ultrasonic wave, oil pollution treatment by ultrasonic wave, wax prevention by ultrasonic wave, plugging removal by ultrasonic wave, and viscosity reduction of heavy oil by ultrasonic wave. , The main principle of ultrasonic demulsification technology is that oil and water particles continuously move to the wave belly and node due to the cavitation effect, thermal effect, and displacement effect produced by vibration, and then coalesce to generate water and oil droplets with larger diameters, and finally separate the oil and water by gravity. The application of ultrasonic technology greatly promotes the demulsification and dehydration effect of emulsion. Through ultrasonic cavitation, the macromolecular hydrocarbons in heavy oil can be cracked into small molecular hydrocarbons, which can realize the separation of crude oil and sludge. , Ultrasonic plug removal technology is widely used in China’s oilfields.…”
Section: Introductionmentioning
confidence: 99%
“…Some of recent new downhole tools used for field-scale operation along with the key problems that could affect the widespread application of ultrasonic oil production technique in China are summarized by Wang and Yin. 32 Recently, promising results in oil removal from oily sludge were shown using ultrasonic stimulation in pilot-scale tests. 33 By and large, most of these studies have concluded that acoustic stimulation has produced promising results.…”
Section: Introductionmentioning
confidence: 99%
“…Field experiments reported by Nikolaevskiy et al suggest that vibrations have altered oil/water production characteristics at distances as much as 200 km from the vibration source such as natural seismic events or artificial explosions. Some of recent new downhole tools used for field-scale operation along with the key problems that could affect the widespread application of ultrasonic oil production technique in China are summarized by Wang and Yin . Recently, promising results in oil removal from oily sludge were shown using ultrasonic stimulation in pilot-scale tests .…”
Section: Introductionmentioning
confidence: 99%